Lessons Learned from Autopsying an Unidentified Body with Iodine‐125 Seeds Implanted for Prostate Brachytherapy1. Issue 2 (22nd November 2016) - Idota, Nozomi; Nakamura, Mami; Masui, Koji; Kakiuchi, Yasuhiro; Yamada, Kei; Ikegaya, Hiroshi
Abstract: We report here lessons learned from an autopsy case involving radioactive materials. We performed an autopsy of an unidentified mummified man with no available medical history whom from imaging findings we suspected had received radioactive seed implants for prostate brachytherapy. We returned the excised prostate and seeds to the body. A few days later, the body was identified by DNA matching and cremated. According to the man's medical record, he had undergone iodine‐125 seeds implantation for prostate cancer 11 months earlier. We should have removed the radioactive seeds from the body to prevent radiation exposure to the bereaved family and/or environmental pollution due to cremation. Surprisingly, one seed was found in the stored prostate specimen. Forensic experts should be cognizant of the risk of both radiation exposure in the autopsy room and environmental pollution. We must remain abreast of the latest advances in medicine.